Regulation of Gastric Metaplasia, Dysplasia, and Neoplasia by Bone Morphogenetic Protein SignalingSummary - Andrea Todisco (Cellular and Molecular Gastroenterology and Hepatology, 2017)
The bone morphogenetic proteins, (BMP)s are regulatory peptides that have significant effects on the growth and differentiation of gastrointestinal tissues. In addition, the BMPs have been shown to exert anti-inflammatory actions in the gut and to negatively regulate the growth of gastric neoplasms. The role of BMP signaling in the regulation of gastric metaplasia, dysplasia and neoplasia has been poorly characterized. Transgenic expression in the mouse stomach of the BMP inhibitor noggin leads to decreased parietal cell number, increased epithelial cell proliferation, and to the emergence of SPEM. Moreover, expression of noggin increases Helicobacter-induced inflammation and epithelial cell proliferation, accelerates the development of dysplasia, and it increases the expression of signal transducer and activator of transcription 3 (STAT3) and of activation-induced cytidine deaminase (AID). These findings provide new clues for a better understanding of the pathophysiological mechanisms that regulate gastric inflammation and the development of both dysplastic and neoplastic lesions of the stomach. Keywords: Cellular Differentiation, Cellular Proliferation, Gastric Inflammation, Cytokines, Chemokines